Tindakan Pengamanan Perdagangan (Safeguard) Terhadap Impor Terigu Menurut Prinsip Gatt/Wto di Indonesia - Taufiq, Muhammad (Jurnal Restorative Justice, 2021)
The Safeguard measures against the import of wheat flour in accordance with the General Agreement On Tariffs And Trade (GATT / WTO Principles) in Indonesia. This research aimed to investigate whether Indonesia's safeguard measures against the import of wheat flour was in accordance with the Principles set out in the GATT / WTO and how the implementation of such safeguard measures based on GATT / WTO stipulation. The research type was normative, and it used primary and secondary legal materials. The data were analyzed qualitatively using content analysis techniques. The research also applied the case approach, the statute approach and the concept approach. The research result indicated that the Indonesian safeguard measures against the wheat flour import had fulfilled the requirements of both the procedural requirement in the stages of the investigation, notification, and consultation, and the substantive requirement, such as the increases of wheat flour, the serious loss and the cause and effect relationship. The safeguard measures of the trade had been implemented in two forms, i.e. provisional safeguard measures in the form of ad-valorem duty, which was 20% from the value of the imports, and the safeguard measures in the form of quota with the exception of the developing countries whose market share was less than 3% of the total volume of imports or collectively their market share did not exceed 9%. The restriction of the quota had not violated the principle of Prohibition of quantity since the internal wheat flour industry suffered from a serious loss which was difficult to repair as the result of the increase of the wheat flour imports. The exceptions stipulated in article XIX GATT, 1947, had confirmed that if the industry of importing country had suffered from a serious loss as the result of the import increase, then the concerned country may not be subject to this principle.